2003
DOI: 10.1016/s0378-1097(03)00300-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of nitrogen-fixingPaenibacillusspecies by polymerase chain reaction–restriction fragment length polymorphism analysis of part of genes encoding 16S rRNA and 23S rRNA and by multilocus enzyme electrophoresis

Abstract: Forty-two strains representing the eight recognized nitrogen-fixing Paenibacillus species and 12 non-identified strains were examined by restriction fragment length polymorphism (RFLP) analysis of part of 16S and 23S rRNA genes amplified by polymerase chain reaction (PCR). Eleven different 16S rDNA genotypes were obtained from the combined data of RFLP analysis with four endonucleases and they were in agreement with the established taxonomic classification. Only one group of unclassified strains (Group I) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 23 publications
0
20
0
1
Order By: Relevance
“…39,40 Moreover seasonal dynamics in the Vibrio population could be investigated using RFLP analysis. 41 On the phylogenetic tree, the representative isolates of the BBA or AAC type groups each form a single cluster relating to genus Comamonas or genus Pseudomonas respectively, whereas those of the BAA type group did not relate to each other and formed five clusters (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Moreover seasonal dynamics in the Vibrio population could be investigated using RFLP analysis. 41 On the phylogenetic tree, the representative isolates of the BBA or AAC type groups each form a single cluster relating to genus Comamonas or genus Pseudomonas respectively, whereas those of the BAA type group did not relate to each other and formed five clusters (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Its plant growth-promoting activity is often ascribed to nitrogen fixation, production of antimicrobial compounds against plant pathogens, and secretion of hydrolytic enzymes that can enhance the availability of nutrients to the plants (5,15,17). There is also evidence that certain Paenibacillus strains produce plant growth hormones, such as cytokinin and auxin (6,11,16,20).…”
mentioning
confidence: 99%
“…The RFLP analysis of 16S rDNA sequences was used to classify various bacterial groups, such as celluloselytic bacteria, 15,16 bacterioplankton, 32 and nitrogen-fixation bacteria isolated from solids. 33,34 In the present study, the RFLP analysis of DMAA decomposing bacteria revealed that 27 isolates obtained from Lake Kahokugata and Lake Kibagata were classified into 12 types. Moreover, no RFLP type was common between Lake Kibagata and Lake Kahokugata, suggesting that the composition of DMAA decomposing bacteria would be specific for each lake.…”
Section: Discussionmentioning
confidence: 55%